The complex landscape of DMD mutations: moving towards personalized medicine - Gatto, Francesca; Benemei, Silvia; Piluso, Giulio; Bello, Luca (Frontiers in Genetics, 2024)
Duchenne muscular dystrophy (DMD) is a severe genetic disorder characterized by progressive muscle degeneration, with respiratory and cardiac complications, caused by mutations in the DMD gene, encoding the protein dystrophin. Various DMD mutations result in different phenotypes and disease severity. Understanding genotype/phenotype correlations is essential to optimize clinical care, as mutation-specific therapies and innovative therapeutic approaches are becoming available.Disease modifier genes, trans-active variants influencing disease severity and phenotypic expressivity, may modulate the response to therapy, and become new therapeutic targets. Uncovering more disease modifier genes via extensive genomic mapping studies offers the potential to fine-tune prognostic assessments for individuals with DMD.This review provides insights into genotype/phenotype correlations and the influence of modifier genes in DMD.